Transcanal Endoscopic Ear Surgery for Excision of a Facial Nerve Venous Malformation With Interposition Nerve Grafting: A Case Report. Issue 6 (July 2017) - Wick, Cameron C.; Sakai, Mark; Richardson, Timothy E.; Isaacson, Brandon
Abstract : Objective: To illustrate a novel approach for the surgical management of a venous malformation of the facial nerve, including interposition nerve grafting, via an exclusively transcanal endoscopic ear surgery (TEES) approach. Patient: Thirty nine-year-old woman with a preoperative House–Brackmann (HB) grade IV facial paresis secondary to a facial nerve tumor. Intervention(s): Surgical excision and interposition nerve graft via a transcanal endoscopic approach. Main Outcome Measure(s): Completeness of resection, approach morbidities, and facial nerve outcome. Results: The TEES approach provided wide exposure of the facial nerve from the geniculate ganglion through the mastoid segment. This visualization facilitated gross total tumor resection, incus interposition ossicular reconstruction, and placement of an interposition nerve graft. The nerve graft was positioned in the fallopian canal and was secured at both ends with surgicel. The patient had no postoperative complications. At 11-month follow-up her facial function had returned to HB grade IV. Conclusions: This is the first report of resecting a venous malformation of the facial nerve with concomitant interposition nerve graft reconstruction via an exclusively endoscopic approach. This report adds to the growing body of evidence that TEES can manage diverse middle ear and lateral skull base pathology. Additional studies are needed to fully elucidate the risk-benefit profile of this technique.